Node.js - The Complete Guide - Schwarzmüller, Maximilian (Packt Publishing, 2019)
Master Node.js to build REST APIs, GraphQL APIs, add authentication, use MongoDB, SQL, and much more! About This Video If you have no Node.js experience, you'll love this course because it starts with zero knowledge assumed. It's the perfect course to become a Node.js developer If you have basic Node.js experience, this course will help you get insights into the basic modules quickly and delve into advanced topics covered in the course In Detail Join the most comprehensive Node.js course. Node.js is probably the most popular and modern server-side programming language you can learn these days! Node.js developers are in high demand as this language is used for everything from traditional web apps with server-side rendered views over REST APIs through to GraphQL APIs and real-time web services. Not to mention its applications in build workflows for projects of all sizes. This course will teach you all of that! Right from scratch with zero prior knowledge assumed. Though if you do bring some knowledge, you'll, of course, be able to quickly jump into the course modules that are most interesting to you. All topics and features of the course will be shown and used in these projects and so you'll learn about them in a realistic environment. Here's what you'll learn in this course: Node.js basics and basic core modules, parsing requests and sending responses Rendering HTML dynamically (on the server) and using Express.js Working with files and generating PDFs on the server (on-the-fly) File upload and download and using the Model-View-Controller (MVC) pattern Using Node.js with SQL (MySQL), Sequelize, NoSQL (MongoDB), and Mongoose Working with sessions and cookies, user authentication, and authorization Sending e-mails, validating user input, and data pagination Handling payments with Stripe.js and building REST APIs Authentication and file upload in REST APIs Building GraphQL APIs and authentication in GraphQL APIs File upload in GraphQL APIs Building a real-time Node.js app with WebSocket Automated testing (unit tests) and deploying a Node.js application Prerequisites: - No Node.js knowledge is required at all No other programming language knowledge (besides JavaScript, see next point) is required Basic JavaScript knowledge is assumed though you should at least be willing to pick it up whilst going through the course. A JS refresher module exists to get you up to the speed with the latest syntax quickly Basic HTML with CSS knowledge will be helpful.